(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The main aim is evaluation of illumination intensity for side emitting plastic optical fibres in dependence on the distance from light source. The special device for measurement of light intensity on surface and cross section at various distances from light source is described. The dependence of surface and cross section light intensity on the distance from light source is expressed by the exponential type model with two parameters; it is illumination intensity in the input into fibre and fibre attenuation factor. For textile structures with optical fibres the illumination intensity is evaluated as well. It was found that illumination intensity of textile structures is very different. It is dependent on the trajectory of optical fibre in textile structure. The highest illumination intensity is for straight fibre in textile with lower waviness.